Distribution of Leptopharsa heveae in rubber tree at São Paulo State, Brazil - Cividanes, Francisco Jorge; Fonseca, Fernando da Silva; Santos, Terezinha Monteiro dos (Pesquisa Agropecuaria Brasileira, 2004)
The objective of this work was to determine the within-plant and seasonal distributions of Leptopharsa heveae Drake & Poor, 1935 (Hemiptera: Tingidae) in rubber tree, Hevea brasiliensis Müell Arg., located in Pindorama, SP. The sampling was carried out considering leaves of internal and external parts of branches located in the upper, medium and lower sections of the north and south sides of rubber trees. The highest density of nymphs was observed from March to May and from October to November, the same occurring in adults from March to July and during November. The similar distribution of L. heveae on the different parts of the rubber trees facilitates sampling activities. Nymphs and adults can be sampled from leaves on the external part of branches located in the lower section of the north or south side of rubber trees.